Right thyroid lobed cyst in a middle-aged woman: A case report - Afodun, Adam Moyosore; Quadri, Khadijah Kofoworola; Okesina, Akeem Ayodeji; Ojewale, Abdulfatai Olakunle; Bakare, Airat Adeola; Eze, Ejike Daniel; Ojuolape, Samsudeen Gbenga; Odoma, Saidi (Journal of Biomedical Sciences, 2020)
Background: Thyroidal ultrasound has been used to detect neck lesions and nodules for decades. However, cystic thyroid disease is rare with few reported series. Different consensus exists concerning availability of medical treatment and the limited role of surgical management. Case presentation: We present a 31-year-old female with obvious neck swelling and dysphagia. Ultrasound diagnosed a suspected colloidal thyroid cyst in the right lobe. The hypoechoic cystic mass measures 3.2 cm x 3.6 cm on frozen sonogram, with evidence of bilateral (cervical) lymphadenopathy. Thyroid cystic nodule viewed via sonar corresponds to detected mass finding on observation and palpitation. Researchers have recently standardized Thyroid-Imaging- Reporting and Data System (TIRADS), mostly in the United States. Conclusion: If Fine Needle Aspiration (FNA) and hormone therapy fail, cysts larger than >2.8cm may require surgical intervention, especially when there is a danger of great-vessel compression.